Editorial: Globalization, Human Security and The Value of Education - Mahayasa, Dias Pabyantara Swandita; Utami, Arum Tri (Fakultas Ilmu Sosial and Ilmu Politik Universitas Jenderal Soedirman, 2023)
Editorial: Globalization, Human Security and The Value of Education